Parasitóides de Chrysomya megacephala (Fabricius) coletados em Itumbiara, Goiás Parasitoids of Chrysomya megacephala (Fabricius) collected in Itumbiara, Goias, Brazil - Carlos H Marchiori (Universidade de São Paulo, 2004)
Foram determinadas as espécies de parasitóides associadas com Chrysomya megacephala, coletados com isca de rins de bovino, em Itumbiara, Estado de Goiás. As pupas foram obtidas pelo método de flutuação, individualizadas em cápsulas de gelatina e mantidas até a emergência das moscas e/ou dos parasitóides. A prevalência total de parasitismo foi de 18,6%. Brachymeria podagrica, Nasonia vitripennis e Pachycrepoideus vindemiae apresentaram uma freqüência de 8,6%, 8,6% e 1,4%, respectivamente. Relata-se a primeira ocorrência de Brachymeria podagrica em pupas de Chrysomya megacephala. This study determined the species of parasitoids associated with Chrysomya megacephala, collected on bovine kidney baits, in Itumbiara, State of Goias, Brazil. The pupae were obtained by flotation. They were individually placed in gelatin capsules until the emergence of the adult flies or their parasitoids. The overall prevalence of parasitism was 18.6%. Brachymeria podagrica, Nasonia vitripennis and Pachycrepoideus vindemiae presented frequencies of 8.6%, 8.6% and 1.4%, respectively. This work reports for the first time the occurrence of Brachymeria podagrica in pupae of Chrysomya megacephala.